The effect of soft tissue augmentation on the clinical and radiographical outcomes following immediate implant placement and provisionalization: a systematic review and meta-analysis - Paolo De Angelis; Paolo Francesco Manicone; Edoardo Rella; Margherita Giorgia Liguori; Silvio De Angelis; Sileno Tancredi; Antonio D'Addona (SpringerOpen, 2021)
Abstract Background Nowadays, due to the esthetic and social demands of patients, conventional staged protocols seem to be increasingly replaced by faster, one-step protocols. The purpose of the present systematic review is to assess the peri-implant soft tissue changes after immediate implant placement and provisionalization (IIPP) comparing patients treated with or without a sub-epithelial connective tissue graft (SCTG) when replacing a single tooth in the esthetic region. Methods The present systematic review was written following the PRISMA checklist. Immediate implants placed with a connective tissue graft and without one were compared. The researched primary outcomes were the mid-buccal mucosa level (MBML) facial soft tissue thickness (FSTT) and marginal bone loss (MBL). The weighted mean differences (WMD) were estimated for all three outcomes. Results The change in the mid-buccal mucosa level in the intervention group was significantly higher (WMD 0.54; 95% CI 0.33-0.75), with no indication of heterogeneity (I2 = 16%). The facial soft tissue thickness increased significantly in the intervention group (WMD 0.79; 95% CI 0.37-1.22). The marginal bone loss was significantly higher in the control group (WMD 0.13; 95% CI 0.07-0.18), with no indication of heterogeneity (I2 = 0%). Conclusions The results of the meta-analyses showed a statistically significant reduced change of the marginal bone loss and vestibular recession, as well as higher soft tissue thickness, when a graft was used. The included studies had a short observation time; therefore, studies with longer follow-ups are needed to confirm these findings.